ANALISIS FILSAFATI PENDIDIKAN BERBASIS LIBERAL-PROGRESIVISME - Supriyono Purwosaputro (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2023)
The independent campus curriculum and independent learning are currently triggering changes in the education system in Indonesia. The reason is, the competence of students in Indonesia is not all ready to undergo this system change. On the other hand, there is also a dilemma faced by educators who are "triggers of knowledge" in the implications of the independent learning curriculum, educators are required to be able to meet all the needs of students and provide freedom for students to choose the field they like. The hope is that students can have adaptive power that can be absorbed in the world of work. However, not a few educators have not been able to meet these achievements due to several factors. Despite all these things, MBKM has a positive impact in terms of efforts to restore basic human potential in students. It is this potential that is the divine nature that must be maintained and developed. Through philosophical analysis, researchers try to decipher the basic concepts of education basicly by liberalis progressivime with qualitative type research. The approach used by researchers is the basic approach of the philosophy of ontology, epistemology, and axiology. Thus, the philosophical analysis is expected to be able to clarify the common thread that is the problem of education today.